Teologi Kepemimpinan Dalam Surat Al-Maidah 5 - Oki Setiana Dewi (AL-KAINAH: Journal of Islamic Studies, 2022)
The hectic discussion regarding the interpretation of Surah al Maidah verse 51 has seized the attention of the author to re-examine the linguistic meaning and context of the verse. In this article, the writer tries to look at the textual, contextual meaning, by considering its socio-psycho-historical elements to be brought into the maudhui (thematic) interpretation, so that the meaning it gives rises to is neutral and universal. This is because the concept of leadership must combine transcendental and humanist values, thus opening a new paradigm for contextual understanding of verses that can color the vision of monotheism as the face of a peaceful Islam, which upholds humanist values, which sees humans as divine beings who believe in themselves. rahmatan lil alamin. In the contextual study of Surah al Maidah verse 51, the author sees that there is no link between the verse and leadership, but the psycho-socio-historical approach implies the need for ethics for a leader who must have trustworthiness, be fair and obey religion. In the end, the success of a leader lies not only on the side of his leadership, but on how much good influence he can give to society and the environment.